Lao People Democratic Republic development effectiveness brief. (Metro Manila, Philippines Asian Development Bank, 2017)
ADBs assistance has helped the country secure rice self sufficiency, upgrade roads, improve health, education, water and sanitation services, strengthen the public and private sectors, protect natural resources, and build strong links with neighboring countries. ADB has provided loan and grant assistance of nearly 2.3 billion and technical assistance of around 156 million, and remains a partner of the Lao PDR as the country seeks to graduate from Least Developed Country status by 2020. This publication details ADBs operations across major sectors, exploring gains made in key areas, as well as challenges that remain.
Keywords: Public administration -- Lao People Democratic Republic; Economic development; Electronic books